The Influence of Ethnomathematics Based Problem Based Learning (PBL) Model on Gedongsongo Temple Objects on the Creative Thinking Ability of Junior High School Students in View of Self-Confidence - Bayu Murti Suryonegoro; Isti Hidayah (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: In analyzing the relationship between the influence of the Problem-Based Learning (PBL) learning model based on ethnomathematics learning at Gedongsongo Temple on the creative thinking abilities of class IX junior high school students regarding self-confidence. Methodology: The subjects of this study were Junior high school 1 Jambu students. The research method used is quasi-experimental and posttest-only control design research. Data collection techniques using test and non-test instruments in the form of questionnaires. Quantitative data analysis begins with a prerequisite test using the normality and homogeneity tests. Test the hypothesis using the proportion test and test the regression analysis. Main Findings: There is a difference in Creative Thinking Ability and a difference in self-confidence which is more increased in applying the problem-based learning model based on Gedongsongo Temple ethnomathematics in class IX junior high school students. Thus, there is a relationship between the influence of the Gedongsongo Temple ethnomathematics problem-based learning model on the creative thinking abilities of class IX junior high school students regarding self-confidence. Novelty/Originality of this study: The expository model through the teacher-centered approach is believed to be unable to empower students' creative thinking abilities and self-confidence, so creative thinking skills and self-confidence are still low, and students do not play an active role in the process of studying the material in class. Therefore, there needs to be an update using the PBL model with ethnomathematics to improve creative thinking skills.